AB0105 Doxycycline and dexamethasone-induced reprogramming of peripheral blood mononuclear cells in a model of arthritis with the systemic manifestations in wistar rats. (15th June 2017) - Litvitskiy, P; Sakharov, V; Alexeeva, E; Mayansky, N; Zakirov, R
Abstract : Background: The systemic juvenile idiopathic arthritis (sJIA) is a problem with high social significance all over the world. Targeted cell reprogramming becomes one of the most important lines for modern medicine and can be regarded as an origin for new highly improved treatment strategy of sJIA. As rat monocytes exhibited CD163 expression in a similar level with that shown for peritoneal macrophages [1], we decided to use CD163 as a key factor indicating cell reprogramming in the study. Objectives: To investigate the dynamical changes in subpopulations of peripheral blood mononuclear cells (PBMC) and to assess doxycycline and dexamethasone effects in a model of arthritis with the systemic manifestations. Methods: Animal model [2] was adapted in 24 Wistar rats (males, 6 month old). On the day of the last stimulation all the rats were divided into 3 equal groups and additional subcutaneous (s.c.) injections were performed as follows: DOXY-group – doxycycline (50 mg/kg, Saratov, Russia), DEXA-group – dexamethasone (4 mg/kg, KRKA, Slovenia), control group – 0, 9% sodium chloride solution (Belarus). The s.c. injections were repeated on Day 54. Time points were 0, 21, 41, and 55 Days. PBMC were assessed by flow cytometry (BD FACSCanto II, USA) according to manufacturer's instructions. Staining was performed with FITC Anti-Rat CD11b (BD Pharmingen), anti-rat CD68 RPE (Serotec, UK), anti-rat CD163 ALEXA FLUOR 647 (Serotec, UK). CD11b+CD68+ and CD11b-CD68+ cells were regarded as monocytes and circulating dendritic cells consequently. At the termination animal organ masses were measured. Results: Up to Day 55 proportions of CD163+ in CD11b+CD68+ population changed synchronically in all groups. On Day 55 the proportions (in comparison with the data of Day 41) were significantly higher in DEXA-group (p<0, 05) but didn't change in DOXY- and control groups (p>0, 05). Cell reprogramming was also observed in population of CD11b-CD68+. So, on Day 41 the proportions of CD163+ cells in CD11b-CD68+ population were significantly increased (in comparison with the data of Days 0 and 21) in DOXY- and DEXA-groups (p<0, 05) but not in control group (p>0, 05). Mentioned changes were subsequent with other parameters of inflammation. We observed significantly lower heart masses in DOXY- and DEXA-groups (median=0, 63 and 0, 635g consequently) in comparison with control group (median=0, 74g) (p<0, 05), but no difference between DOXY- and DEXA- groups (p>0, 05). Conclusions: In a model of arthritis with the systemic manifestations in Wistar rats we demonstrated that subpopulations of PBMC (CD11b-CD68+ and CD11b+CD68+) underwent reprogramming. Doxycycline and dexamethasone modyfied the dynamics of the reprogramming. In DOXY- and DEXA-groups there were lower heart masses than in the control group, the last fact is subsequent with the data by De P. et al. [3]. We can speculate that monocytes and dendritic cells undergo reprogramming (CD163neg and CD163+) in a similar way with M1 and M2 macrophages. References: Moghaddami M, Cleland LG, Mayrhofer G. Int Immunol. 2005; 17(8):1103–15. Litvitskiy P, Sakharov V, Alexeeva E, et al. Annals of the Rheumatic Diseases. 2016;75:264. De P, Roy SG, Kar D et al. J Endocrinol. 2011;209(1):105–14. Disclosure of Interest: None declared